Taman Baca dan Belajar “Ransel Buku” Sebagai Aksi Nyata Menumbuhkan Kecintaan Anak Pada Buku dan Kegiatan Literasi - Brigita Manik; Wildan Khairul Umam; Fery Irawan; Meyeti Veronica; Misnawati Misnawati; Alifiah Nurachmana; Nirena Ade Christy (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
This research aimed to describe the real action of the Reading and Learning center “Ransel Buku” Center to increase children's love of books and literacy activities in Petuk Katimpun Village, Jekan Raya District, Central Kalimantan Province so that it can become an inspiration and motivation for readers to actively participate in foster and promote a love of books and literacy activities for the community, especially for children in the surrounding environment. This research was conducted using a descriptive qualitative method. The data collection method in this study was the interview method, namely by conducting a dialogue with the founder of the Reading and Learning center “Ransel Buku” and making direct and indirect observations. From the results of the data obtained, it can be concluded that Reading and Learning center “Ransel Buku” from its inception to today has provided real action in fostering children's love of books and literacy activities. This can be seen from the various activities carried out such as book reading activities, teaching and learning activities, “Ransel Buku” boat, and many others. In addition, the number of reading books available in Reading and Learning “Ransel Buku” ack has reached 8,000 book titles. The Reading and Learning center“Ransel Buku” has won many awards both at the provincial and national levels.